2013
DOI: 10.1016/j.cyto.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise modulates lipid plasma profile and cytokine content in the adipose tissue of tumour-bearing rats

Abstract: Cancer cachexia is a multifactorial syndrome characterised by progressive weight loss, frequently accompanied by anorexia, sarcopenia, and chronic systemic inflammation. The white adipose tissue is markedly affected by cachexia and contributes to this syndrome throught the secretion of pro-inflammatory factors which reach the adjacent tissues and the circulation. A nonpharmacologic intervention that may attenuate cancer cachexia is chronic physical activity, but the effect of resistance training upon adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 45 publications
4
53
1
5
Order By: Relevance
“…These findings are in opposition to the results of the present study. Donatto et al 14 analysed the expression of IL-6 protein in muscle from healthy mice and with induced tumour subjected to training on vertical overhead ladder and overload with 75-90% of body weight, found that mice with tumours presented IL-6 levels 90% higher than the control rats.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are in opposition to the results of the present study. Donatto et al 14 analysed the expression of IL-6 protein in muscle from healthy mice and with induced tumour subjected to training on vertical overhead ladder and overload with 75-90% of body weight, found that mice with tumours presented IL-6 levels 90% higher than the control rats.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies in experimental models reported that exercise training can improve symptoms of cachexia 6,7 . Our results show that endurance training is effective to improve the physical condition and the biochemical markers of cachexia in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different programs of resistance training for rats have used distinctive protocols based on the number of sessions per week (3–4 times a week) with intervals of 48 hours between the sessions ( 13,14,16 ). Previous studies used the model of climbing a vertical ladder during 8 weeks, with 48 hours interval between sessions and the maximum overload tests performed in each session (24 maximum overload tests during the program) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%